2010
DOI: 10.1007/s00441-010-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces enhanced expression of resistin in human U937 monocyte-like cell line by MAPK- and NF-kB-dependent mechanisms; the modulating effect of insulin

Abstract: Resistin has emerged as a significant local and systemic regulatory cytokine involved in inflammation. In diabetic patients, the serum resistin level is increased, monocytes/macrophages being an important source of resistin production. We therefore hypothesize that high glucose concentrations (HG) regulate resistin expression in human monocytes. Our aim has been to uncover the potential signalling pathways involved in this process. We have also questioned whether insulin has an effect on the regulation of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…High glucose concentrations also upregulated resistin gene expression and protein levels in the human U937 monocytic cell line, an effect mediated by MAPK and NF-kB-dependent mechanisms [33]. In contrast, insulin diminished resistin expression by 30–37% in 3T3-L1 mouse adipocytes acting possibly through the Phosphoinositide (PI)-3, ERK, or p38-MAP- kinases pathways [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…High glucose concentrations also upregulated resistin gene expression and protein levels in the human U937 monocytic cell line, an effect mediated by MAPK and NF-kB-dependent mechanisms [33]. In contrast, insulin diminished resistin expression by 30–37% in 3T3-L1 mouse adipocytes acting possibly through the Phosphoinositide (PI)-3, ERK, or p38-MAP- kinases pathways [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…This transition also indicates the condition where cortisol levels start declining and reach basal levels (L1) by time t 1 . It is important to note that excess of glucose levels are known to increase production of pro-inflammatory cytokines [65], [66]. Blood glucose levels might be one of the mechanisms involved in controlling cortisol levels (since excess of cortisol can create a hyperglycemic state).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NF-κB, HG can also activate JNK, 41 which is an important player in inflammation and regulates the transcription of a number of inflammatory cytokines. 35,42 We observed that not only HG activated JNK in mesangial cells, podocytes, tubular cells, and macrophages, but renal tissue from T2D and T1D presented with activated JNK as well, and FGF1 prevented JNK activation in each of those cases.…”
Section: Disussionmentioning
confidence: 99%